TEACHER’S COMPETENCE IN CHOOSING ASSESSMENT METHODS AT SMAN 5 PADANG - Fitrianti, Dela; Yulmiati, Yulmiati (TELL - US JOURNAL, 2017)
This research explained about teacher competence in choosing assessment methods. This research is qualitative research where the participants are three English teachers at SMA N 5 Padang. The instruments of this research were document chekclist and interview. The result of this research is teachers at SMAN 5 Padang have competence in choosing assessment methods. Their assessment methods also demand the content of validity. In other words, they often used all kinds of assessment methods in the class such as: objective test, essay, written, performance based assessment, self report assessment, oral, assigment and project to assess students at SMAN 5 Padang.